Sosialisasi Peningkatan Brand Awareness Pada UMKM Wisata Kuliner Lego-Lego Center Point of Indonesia Makassar - Emily Nur Saidy; Rustan DM; Dirmansyah Darwin; Rosnani Said; Sri Prilmayanti Awaluddin (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This socialization aims to increase brand awareness of MSMEs at Lego-Lego Centre Point of Indonesia, Makassar. This research combines qualitative and quantitative approaches, with the qualitative method involving literature review, interviews with MSME owners, and on-site observations, while the quantitative method involves visitor surveys and statistical analyses. The results show that culinary MSMEs in Lego-Lego CPI Makassar have low brand awareness, with many MSME owners not understanding the importance of branding strategies and marketing aspects. However, the socialisation conducted succeeded in improving their understanding of brand awareness as well as providing practical skills in managing branding. The use of social media, collaboration with influencers, and attractive product packaging proved effective in increasing brand awareness. Based on the results of this study, it is concluded that increasing brand awareness is very important for culinary MSMEs in Lego-Lego Centre Point of Indonesia. Socialisation involving digital marketing strategies, collaboration with influencers, and attractive product packaging can help MSMEs increase their brand awareness. It is recommended that MSMEs allocate sufficient resources for marketing and branding activities and continue to develop knowledge and skills in managing effective branding strategies. Thus, it is expected that culinary MSMEs in LegoLego CPI Makassar can develop more rapidly and become major players in the culinary tourism industry.